Clinical application of intravesical botulinum toxin type A for overactive bladder and interstitial cystitis - Chen, Jing-Liang (Investig Clin Urol, 2020)
After decades of clinical and basic science research, the clinical application of botulinum toxin A (Botox) in urology has been extended to neurogenic detrusor overactivity (NDO), idiopathic detrusor overactivity, refractory overactive bladder (OAB), interstitial cystitis/bladder pain syndrome (IC/BPS), lower urinary tract symptoms, benign prostatic hyperplasia, and neurogenic or non-neurogenic lower urinary tract dysfunction in children. Botox selectively disrupts and modulates neurotransmission, suppresses detrusor overactivity, and modulates sensory function, inflammation, and glandular function. In addition to motor effects, Botox has been found to have sensory inhibitory effects and anti-inflammatory effects; therefore, it has been used to treat IC/BPS and OAB. Currently, Botox has been approved for the treatment of NDO and OAB. Recent clinical trials on Botox for the treatment of IC/BPS have reported promising therapeutic effects, including reduced bladder pain. Additionally, the therapeutic duration was found to be longer with repeated Botox injections than with a single injection. However, the use of Botox for IC/BPS has not been approved. This paper reviews the recent advances in intravesical Botox treatment for OAB and IC/BPS.